Penerapan Bimbingan Kelompok Dengan Dsikusi Kelompok Untuk Mengurangi Kecenderungan Cinderella Complex Siswi SMA - Arifin, Deasy Dwi Cahyaningtyas (JURNAL KONSELING GUSJIGANG, 2018)
Group guidance is an aid to individuals carried out in group situations. Group guidance can be the delivery of information or group activities to discuss issues of education, work, personal, and social. Group discussion is a planned conversation between three or more people in order to solve a problem or to clarify a problem, under the leadership of a leader. In this research will use group discussion. The use of group discussions for students with a cinderella complex helps their students to share with each other. Cinderella complex is a stance and feeling that is mostly depressed so that women can not and do not dare to fully utilize the ability of the brain and creativity.